Antibacterial activity of compounds from Azolla pinnata extracted using Soxhlet and Supercritical Fluid (SFE) methods - Mahyuddin, Husna Sabrina; Roshidi, Muhammad Ameerul Haqim; Ferdosh, Sahena; Noh, Abdul Latif (Zibeline International Publishers, 2020)
The propagation, extraction, and antibacterial studies of Azolla pinnata were carried out in this study. The propagation involved two fertilizers, which were chicken manure and inorganic AB fertilizer. The dry yield was extracted using two methods, which were Soxhlet and supercritical fluid extraction (SFE). Methanolic extracts were obtained and subjected to several antibacterial tests, which include the disk diffusion assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests, against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The results showed that AB fertilizer produced more dry yield compared to chicken manure. The extract yield from Soxhlet exhibited a higher yield than that of SFE, recording its highest at 21.20%. The findings of antibacterial tests revealed that all extracts inhibited the growth of B. subtilis and S. aureus, but none showed inhibition against E. coli and P. aeruginosa. The largest diameter of inhibition zone of 2.67 ± 1.53 mm was obtained by E2 (CM-SFE), with a MIC value of 0.125 mg/mL against B. subtilis. High MBC values further confirm that the mechanism of inhibition against B. subtilis and S. aureus were due to the bacteriostatic properties of the extracts tested.